2009
DOI: 10.1111/j.1365-2710.2008.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

A limited sampling strategy for estimating mycophenolic acid area under the curve in adult heart transplant patients treated with concomitant cyclosporine

Abstract: The proposed three time-point equation to estimate AUC will be helpful in optimizing immunosuppressive therapy in heart transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 40 publications
1
50
0
Order By: Relevance
“…Predose assessment of MPA is a commonly used alternative to MPA AUC 0-12 . However, correlations between predose concentrations and MPA AUC 0-12 are relatively weak (r 2 = 0.4-0.5), 9 and there is greater within-patient variability for predose concentrations than for AUC 0-12 . Abbreviated AUC strategies have been proposed to represent the best of both worlds, yielding greater accuracy than predose measurements, although being less cumbersome than a 12-hour sampling strategy.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Predose assessment of MPA is a commonly used alternative to MPA AUC 0-12 . However, correlations between predose concentrations and MPA AUC 0-12 are relatively weak (r 2 = 0.4-0.5), 9 and there is greater within-patient variability for predose concentrations than for AUC 0-12 . Abbreviated AUC strategies have been proposed to represent the best of both worlds, yielding greater accuracy than predose measurements, although being less cumbersome than a 12-hour sampling strategy.…”
Section: Introductionmentioning
confidence: 92%
“…For MPA, limited sampling strategies (LSSs) using a predose sample and 2 postdose samples have shown good agreement between the estimated and measured AUC, with correlation coefficients (r 2 ) ranging from 0.84 to 0.95. [9][10][11] Following anecdotal reports describing benefits of MMF in patients with systemic lupus erythematosus (SLE) and lupus nephritis, small studies and finally large, randomized, controlled trials have established the use of MMF in these patients, particularly those with lupus nephritis. 12 MMF use in other autoimmune disease (AID), like antineutrophil cytoplasmic antibody-associated systemic vasculitis, has only been evaluated in smaller studies and in very few randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies agreed with the findings of Ting et al 21 and showed that an LSS using only plasma concentrations within 4 hours of MMF administration provided a good estimation of the AUC of MPA. [22][23][24][25] On the other hand, several reports showed that the plasma concentration at 6 hours (C 6h ) after MMF administration was necessary for a good estimation of the AUC of MPA. [26][27][28][29] Ting et al 21 showed that the predicted AUC should, ideally, be estimated by a few concentration measurements over a short period after administration.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, nine articles presented 25 LSSs derived from patients cotreated with cyclosporine [29][30][31][32][33][34][35][36][37] and four articles presented 53 LSSs derived from patients cotreated with tacrolimus. [38][39][40][41] Patients and Data Collection Table 1 shows the baseline demographic and clinical characteristics of study participants. These were comparable to those of our overall transplant population (data not shown).…”
Section: Limited Sampling Strategiesmentioning
confidence: 99%